UEFA Champions League: an empirical study of goals scored in the 2017/2018 season and the relationship in match results - Cláudio, Rúbio Rodrigues (2021)
Introduction: football games have critical periods. There are times when goals are more frequent and can influence the outcome. Objective: observe the occurrence of goals, characteristics (initial goal, pro, time of occurrence), and the relationship is the result of matches in the UEFA Champions League 2017-2018. Materials and Methods: the 401 goals scored in 125 matches were inserted in a spreadsheet editor and separated as follows: 1-15, 16-30, 31-45, 45+, 46-60, 61-75, 76-90, 90+. Results: goal period and number of goals respectively: 1-15: 64; 16-30: 52; 31-45: 62; 45+: 4; 46-60: 64; 61-75: 75; 76-90: 67; 90+: 13. Being the first goal in the first 15 minutes, 88% of the teams did not lose. After 75 minutes, 78% of the goals were the winning goals. In the goals that occurred in the initial or final periods, 70.4% of the games ended in victory. In 67% of the victories, the team that scored the first goal won. Discussion: a goal impacts the players' technical, tactical, physical, and mental aspects. In the physical, it is suggestive that the higher incidence of goals in the second half is linked to a better resistance, besides impacting on the technical aspect since the motor gestures also depend on less wear. In tactics, whoever scores the first goal could stay organized. In the mental aspect, there is less psychological wear. Conclusion: in the mentioned competition and season, the occurrence of goals in the initial or final periods proved important for the team's victory.